Differences in pre-conception and pregnancy healthy lifestyle advice by maternal BMI: Findings from a cross sectional survey. (November 2016) - Bye, Amanda; Shawe, Jill; Stephenson, Judith; Bick, Debra; Brima, Nataliya; Micali, Nadia
Abstract: Objective: Being underweight at pregnancy commencement is associated with a range of adverse maternal and infant outcomes, as is being overweight or obese, yet it is an aspect of maternal health which has been relatively neglected by healthcare professionals and researchers. We aimed to investigate differences in pre-pregnancy and pregnancy healthy lifestyle advice routinely offered by relevant healthcare professionals, including midwives and GPs, to women across three different BMI categories – underweight, normal, and overweight or obese. Design: A cross-sectional study nested in an antenatal survey of pregnant women. Setting: Antenatal clinics of three National Health Service (NHS) hospitals in London, UK. Participants: Pregnant women at any gestation of pregnancy were invited to participate in the study whilst attending a routine antenatal scan appointment. Measurements: Main outcomes of interest were whether women had sought and/or had been offered healthy lifestyle advice by relevant healthcare professionals before or during the index pregnancy and whether the advice offered had included weight management, tobacco smoking cessation and alcohol intake. Other outcomes included alcohol consumption and tobacco smoking before and during the index pregnancy. Findings: A total of 1173 women completed the survey, with pre-pregnancy BMI data available for 918 (78.3%) women, 632 (69%) of whom were of normal weight, 232 (25%) were overweight or obese, and 54 (6%) were underweight. Overall, 253 (28%) of these women reported they had sought pre-conception advice. Women with a low BMI were offered pre-pregnancy and pregnancy healthy lifestyle advice of a similar content to women with a normal BMI, whereas women with a high BMI were more likely to be offered specific pre-conception and pregnancy advice on healthy BMI (respectively OR 2.55; 95% CI 1.64–3.96: OR 1.79; 95% CI 1.26–2.54), pre-conception healthy diet (OR 1.58; 95% CI 1.06–2.37), reducing alcohol consumption (OR 1.63; 95% CI 1.06–2.51) and smoking cessation (OR 1.62; 95% CI 1.05–2.50). For all women, reported alcohol consumption during pregnancy was lower than pre-conception, but within each BMI group around half of the women reported consuming alcohol at some time during their pregnancy. Key conclusions: Women with a low BMI are no more likely than women with a normal BMI to be advised by health professionals about a healthy lifestyle or a healthy weight for their height before or during pregnancy. In contrast women with a high BMI are more likely to receive such advice. Provision of pre-conception care could provide opportunity to advise women across the weight spectrum of the importance of adopting a healthy lifestyle for optimal pregnancy outcomes, as well as consider management of any pre-existing medical conditions. Implications for practice: Healthy lifestyle advice, including alcohol consumption and smoking cessation, should be offered to women who are underweight before and during pregnancy as well as to women who are overweight or obese, to improve adherence to recommendations to optimise maternal and infant outcomes. Advice should also be tailored to reflect women's ethnic background, which could be an important influence on lifestyle behaviour and weight management. The potential clinical benefit of routine provision of pre-conception care, particularly for women who have a high risk of a poorer pregnancy outcome due to weight status or other medical complications, needs to be explored.